Economic Analysis Of Production And Marketing Of Vegetables In Thiruvananthapuram District - Nagesh SS (Department of Agricultural economics, College of horticulture, 2001)
The present study on "Economic analysis of production and marketing of vegetables in Thiruvananthapuram district" was conducted with a view to examine the costs and returns of vegetable cultivation, employment generation, marketing efficiency, technical efficiency and problems encountered in production and marketing of vegetables. A comparative study of vegetable growers of KHDP and IVDP was also carried out. The data pertains to the year 1999-2000. The total explicit costs for IVDP and KHDP snakegourd growers were Rs. 62711.60 and Rs. 61448.40 respectively. Total implicit cost was worked out at Rs. 64956.90 and Rs. 58140.20 respectively for IVDP and KHDP growers. Bitter gourd was the only crop, which recorded a benefit-cost ratio higher than one at cost C3. The total cost of cultivation (Cost C3) ranged from the lowest of Rs. 64313.70 for amaranth us to as high as Rs. 134135.60 for bittergourd. Bittergourd was the most remunerative crop in the area with a gross return of Rs. 206065.20 for KHDP and a benefit cost ratio of 1.53 at cost C3. Cost of organic manure occupied the highest share of the total cost of cultivation of all the three crops.